Analysis of Employee Engagement in PT Kaltim Prima Coal Indonesia - Utoro, Dyta Tameswari; Gustomo, Aurik (Journal of Business and Management, 2014)
PT Kaltim Prima Coal (KPC) is one of largest mining company in the world, which engages in coal mining and sales for both domestic and international industrial customers. In the midst of the global competition climate, Kaltim Prima Coal recognize that it is their employee who have driven company to move forward and distinguished them from other competitors. The purpose of this research is to find out which factor that affect the employee engagement in KPC and in the end will analyze about factors that need more improvements, in order to maintain the employee engagement within employees in KPC. The result shows that there were 3 factors that really affect the employee engagement in D & E level of management in PT KPC, there were quality of work, inspiration value, and tangible rewards.Keywords: PT KPC, employee engagement, hay model, ASTD